Is a dwarf population of Corythomantis greeningi Boulenger, 1896 (Anura, Hylidae) a new species? - Juncá, Flora Acuña; Carneiro, Maria Conceição Lago; Rodrigues, Nayara Nascimento (Zootaxa, 2008)
We studied the possible existence of a new dwarf species of the monotypic genus Corythomantis, based on tadpole morphology and advertisement call characteristics of two populations from State of Bahia: Serra São José (dwarf adults) and Lages (normal adult size). We compared the tadpole morphology and the advertisement call of Corythomantis greeningi from Lages with the population of Serra São José. We did not find any differences supporting that the population of Lages could represent a new species of Corythomantis. The tadpoles show external morphological characters associated with benthonic habitats and dental formula 5–6(1)/5–8. The advertisement call is composed of one pulsed note with duration of approximately 0.30 s and dominant frequency of approximately 1.00 kHz.